1995
DOI: 10.1007/bf00203680
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem evaluation of four randomly selected automated biopsy devices for transthoracic lung biopsy

Abstract: Automated biopsy devices can obtain high quality lung specimens sufficient for definite histopathologic diagnosis. However, additional clinical studies on the use of automated biopsy devices for lung biopsy are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Currently, the automated cutting needle in tissue-core biopsy is considered to be useful for obtaining specimens of lung nodules for histological evaluation [17]. There are numerous automated cutting needles, and comparisons of performance of various automated biopsy needles have been made [12,13,[18][19][20]. Hopper et al [12] evaluated 20 different automated biopsy needles for use in fresh autopsy cases and reported that performance of the semi-automated biopsy needles, including the Temno needle, was worse than that of the fully automated biopsy needles, including the Monopty needle.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the automated cutting needle in tissue-core biopsy is considered to be useful for obtaining specimens of lung nodules for histological evaluation [17]. There are numerous automated cutting needles, and comparisons of performance of various automated biopsy needles have been made [12,13,[18][19][20]. Hopper et al [12] evaluated 20 different automated biopsy needles for use in fresh autopsy cases and reported that performance of the semi-automated biopsy needles, including the Temno needle, was worse than that of the fully automated biopsy needles, including the Monopty needle.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported better performances of long-throw TCT needles in liver and kidney biopsies of pigs [35] and cadavers [16], whereas an in vivo comparison between TCT and MMT needle showed similar efficacy in liver biopsy [17]. A postmortem evaluation suggested a better performance of the TCT needle in transthoracic biopsy [15], whereas a study evaluating an automated MMT needle reported an overall accuracy of 90.9 %, but no comparison was done with the TCT needle [36]. To our knowledge, there are no in vivo studies comparing the diagnostic yield of the MMT and TCT needles in transthoracic biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors can influence the diagnostic yield of transthoracic biopsy, such as needle size [11], length of the needle path [12], and lesion size [12 -14]. However, the yield of the different types of cutting needles used to perform core biopsy has scarcely been investigated, and mostly in cadavers [15,16]. The various kinds of cutting needles can be divided roughly into two types: the modified Tru-cut-type (TCT) needle, and the modified Menghini-type (MMT) needle.…”
mentioning
confidence: 99%
“…A side-notch of the inner needle is filled with tissue and an outer cannula is then immediately fired, and cuts a core biopsy from the tissue in the notch. The technique has been evaluated in several studies covering both the prostate and other organs [7][8][9][10][11]. However, there are two major disadvantages with the side-notch needle.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the first few millimetres of the needle cuts without being filled with tissue. Several other biopsy instruments have been introduced using essentially the same technique [7][8][9]11,12]. Recently, a new instrument for core biopsies (BioPince, Amedic, Sollentuna, Sweden) has been developed.…”
Section: Introductionmentioning
confidence: 99%